INVESTIGATION OF STRAIN INHOMOGENEITy IN HExA-ECAP PROCESSED AA7075 - KENTLİ, AYKUT; ÖZBEYAZ, KERİM; ÖĞÜT, SERKAN (POLSKA AKAD NAUK, POLISH ACAD SCIENCES, INST METALL & MATER SCI PAS, 2021)
Severe Plastic Deformation (SPD) techniques have been used by researchers for last three decades in order to obtain UltraFine Grained (UFG) materials. Equal Channel Angular Pressing (ECAP) is preferred more than other SPD techniques thanks to its high performance and practicability. Hexa Equal Channel Angular Pressing (Hexa-ECAP) - modified ECAP technique which enables to apply ECAP routes for cylindrical samples properly - was preferred in this study. Within the objective of this study, the effects of coefficient and ram velocity on the mean effective strain and strain inhomogeneity of Hexa-ECAP processed Al7075 aluminium alloy were investigated. Also, the effects of ram velocity and friction coefficient on hardness homogeneity were investigated benefitting from the similarity between the hardness distribution and the strain distribution.
Keywords: Strain Inhomogeneity; Hexa-ECAP; ECAP; SPD; AA7075; CHANNEL ANGULAR EXTRUSION; MICROSTRUCTURAL EVOLUTION; BEHAVIOR; PRINCIPLES; PARAMETERS